Answer: - 63
Explanation:
An arithmetic progression is such that the N-th element is equal to:
An = A1 + (n-1)*R
where A1 is the first term, and R is the difference between two consecutive terms.
We know that
A1 + 9*R = -37
and
A1 + (A1 + R) + (A1 + 2R) + (A1 + 3R) + (A1 + 4R) + (A1 + 5R) = -27
6*A1 + R(1 + 2 + 3 + 4 + 5) = -27
6*A1 + 15*R = -27
so we have two equations:
6*A1 + 15*R = -27
A1 + 9*R = -37
Let's find A1 and R.
First, isolate A1 in the second equation:
A1 = -37 - 9*R
now replace it in the other equation and solve it for R.
6*A1 + 15*R = -27
6*(-37 - 9*R) + 15*R = -27
-222 - 54*R + 15*R = -27
-39*R = -27 + 222 = 195
R = 195/-39 = -5
Now we can find the value of A1:
A1 = -37 - 9*R = -37 - 9*-5 = 8
So now we want to calculate the sum of the first eight terms. we already know that the sum of the first six is -27, so we need to add the seventh and the eigth.
A7 = 8 + 6*-5 = -17
A8 = 8 + 7*-5 = -22
Sum = -27 -17 - 22 = -63